The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1159/000357382
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Autophagy Induced by Rapamycin in Rat Acute Spinal Cord Injury Model

Abstract: Background/Aims: To explore the effects of rapamycin-induced autophagy on apoptosis in a rat model of acute spinal cord injury (SCI), and to explore the effect of rapamycin on apoptosis in primary spinal cord cell culture. Methods: SCI was induced at T10 in female adult Sprague-Dawley rats. After injury was induced, the rats were injected with rapamycin and/or methylprednisolone and were sacrificed at various days after injury. Apoptosis and autophagy were examined with TUNEL staining and electron microscopy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…Consistent with the hypothesis that autophagy is beneficial, but usually impaired, in the context of neurotrauma, rapamycin and other molecules with autophagy-inducing potential (for example, melatonin and retinoic acid) limit CNS damage, support regeneration and improve the restoration of neuromuscular functions in rodents experiencing spinal cord injury (SCI) 95 or subarachnoid haemorrhage (SAH) 9698 . Chemical inhibitors of autophagy, including 3-MA, wortmannin and the antimalarial drug chloroquine (which blocks lysosomal degradation), aggravated neurological damage imposed by SCI or SAH 96,99 , and abolished the neuroprotective effects of autophagy inducers 98,100 .…”
Section: Autophagy As a Therapeutic Targetmentioning
confidence: 75%
“…Consistent with the hypothesis that autophagy is beneficial, but usually impaired, in the context of neurotrauma, rapamycin and other molecules with autophagy-inducing potential (for example, melatonin and retinoic acid) limit CNS damage, support regeneration and improve the restoration of neuromuscular functions in rodents experiencing spinal cord injury (SCI) 95 or subarachnoid haemorrhage (SAH) 9698 . Chemical inhibitors of autophagy, including 3-MA, wortmannin and the antimalarial drug chloroquine (which blocks lysosomal degradation), aggravated neurological damage imposed by SCI or SAH 96,99 , and abolished the neuroprotective effects of autophagy inducers 98,100 .…”
Section: Autophagy As a Therapeutic Targetmentioning
confidence: 75%
“…A better understanding of autophagy regulation by LKE and similar compounds could lead to improved treatment for a host of CNS and peripheral conditions where autophagy dysfunction recently has been implicated, including such diverse conditions as Batten disease (Thelen et al, 2012); diabetic neuropathy (Qu et al, 2014); hearing loss (Menardo et al, 2012); lysosomal storage diseases (Pivtoraiko et al, 2009); muscular dystrophies (De Palma et al, 2012; Bibee et al, 2014); spinal cord injury (Wang et al, 2014); and traumatic brain injury (Sarkar et al, 2014). Work is underway in our laboratory, and others, to test LK derivatives in appropriate preclinical models of these pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that promotion of autophagy confers a neuroprotective function in SCI. 26 Moreover, oxidative stress injury can be relieved by autophagy, whereas apoptosis can be inhibited by the activation of autophagy. Therefore, the effects of calcitriol on attenuating oxidative stress and Effects of calcitriol on SCI K-l Zhou et al decreasing apoptosis after SCI in rats may be mediated through activation of autophagy.…”
Section: Effects Of Calcitriol On Sci K-l Zhou Et Almentioning
confidence: 99%